2013
DOI: 10.1093/rheumatology/ket265
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in gout: a systematic review

Abstract: Objectives. To identify the instruments that have been used to measure health-related quality of life (HRQOL) in gout and assess their clinimetric properties, determine the distribution of HRQOL in gout and identify factors associated with poor HRQOL.Methods. Medline, CINAHL, EMBASE and PsycINFO were searched from inception to October 2012. Search terms pertained to gout, health or functional status, clinimetric properties and HRQOL. Study data extraction and quality assessment were performed by two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 40 publications
(159 reference statements)
4
78
0
3
Order By: Relevance
“…32 A recent study, however, found that the linking relationships for PROMIS Pain Interference and the Brief Pain Inventory were very similar when derived from general population and multiple sclerosis groups. 36,37 Nevertheless, it will be necessary to replicate our study with samples drawn from populations with a higher density of scores at either end of the physical function continuum.…”
Section: Discussionmentioning
confidence: 99%
“…32 A recent study, however, found that the linking relationships for PROMIS Pain Interference and the Brief Pain Inventory were very similar when derived from general population and multiple sclerosis groups. 36,37 Nevertheless, it will be necessary to replicate our study with samples drawn from populations with a higher density of scores at either end of the physical function continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Severe renal failure Therapeutic options (1) Abbreviations: PPI, proton pump inhibitor; others, see TABLE 1 250 mg twice daily) for up to 6 months is support ed by evidence from RCTs and observational stud ies. 39 Patients and physicians need to be aware, however, that there is a risk of neurotoxicity and myopathy with colchicine prophylaxis in patients with renal impairment and in patients receiving statins, so renal function should be assessed be fore prescribing colchicine or NSAIDs.…”
Section: Eular Recommendations For the Management Of Flares In Patienmentioning
confidence: 99%
“…cyclosporine, cimetidine, clarithromycin, eryth romycin, ketoconazole, and verapamil ), and should be used with caution and at low doses in patients taking drugs which are potent inhibitors of P glyco protein or cytochrome P450 3A4 (CYP3A4) (eg, Treat as early as possible (1) Resolution of flare Avoid colchicine (2) Colchicine (2) (1 mg followed 1 hour later by 0.5 mg) NSAID (2) (classic or coxibs + PPI if appropriate) Prednisolone (2) (30-35 mg/d for 3-5 days)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, measures of disease activity including serum urate acid (SUA) levels, frequency of flares, and the presence of tophi have all been linked to higher costs 2,3 . Evidence demonstrates that health-related quality of life (HRQOL) is lower in the gout population when compared with the healthy population, largely attributed to the painful flares and physical disability associated with the disease 2,4 . The global burden of gout is rising; disability-adjusted life-years increased from 76,000 in 1990 to 114,000 in 2010 1 .…”
Section: The Economic Value Of Genetic Testing For Tolerance Of Allopmentioning
confidence: 99%